Protective effect of 21‐aminosteroid pretreatment in peripheral nerve low‐load crush injury in mature and immature rats - Nasser, R.M. (1996)
The effects of U-74006F (tirilazad mesylate), a 21-aminosteroid antioxidant, on injured peripheral nerve were studied. Twenty-two immature and 44 mature rats were divided equally into two groups. The experimental group received two injections of 3 mg/kg of U-74006F at a 2-h interval. The control group received the same volumes of a citrate buffer. A 5-mm segment of the sciatic nerve was subjected to a crush load of 100 g for 2 h. Motor function (sciatic functional index) was assessed to day 48 postoperatively. There was total paralysis of the crushed limb in all rats the first week after crushing. The experimental group had a statistically significant improvement in motor function compared with the controls on days 14, 21, 25, and 28 for the mature rats and on days 11 and 14 for the immature rats. The mature controls attained complete recovery on day 42 and had a significantly slower recovery rate than the immature controls, which had recovered fully by day 25. The recovery rates were almost similar among mature and immature groups pretreated with U-74006F, both of which had fully recovered motor function by day 28. The results indicate that pretreatment with U-74006F can significantly promote peripheral nerve function after low-load crush injury and that the age of the animal influences the rate of peripheral nerve recovery.